The "three-point shooting paradox": An artifact or a real phenomenon? Replication with large-scale National Basketball Association (NBA) data - Morgulev, E. (Psychology of Sport and Exercise, 2024)
Psychological science is often being criticized for failing to reproduce some of its findings. Considering this critique, Iso-Ahola (2024) argues that it is important to establish a demarcation line between artifact and a real phenomenon, recognizing that psychological phenomena are not constant particles that can be definitively declared to exist or not exist upon discovery. In this brief paper, we utilize newly available large-scale data to replicate a finding by Lidor et al. (2022), who reported a psychological effect wherein professional basketball players shoot better under tight defensive pressure rather than free of it. The current analysis of 781,663 three-point shots over 11 seasons in NBA (as compared to 382 shots taken by 12 players during 12 games in the original study) failed to support the idea of the three-point shooting paradox but instead strongly supports the commonsense hypothesis that tight defense hinders shooting performance.